Neopterin as a biomarker of immune response in cancer patients - Melichar, Bohuslav; Spisarová, Martina; Bartoušková, Marie; Krčmová, Lenka Kujovská; Javorská, Lenka; Študentová, Hana (Annals of translational medicine, 2017)
With the advent of immunotherapy the topic of biomarkers of immune response is of high interest. Along with the expression of programmed death ligand 1 (PD-L1) or tumor infiltrating lymphocytes (TIL), biomarkers of macrophage activation could be of interest. Neopterin is a biomarker of immune activation increased in different disorders associated with immune activation, including cancer. Neopterin synthesis is induced by interferon-γ that also induces indoleamine 2,3-dioxygenase (IDO), an enzyme catalyzing catabolism of tryptophan to kynurenine. Increased urinary or serum concentrations of neopterin have been associated with poor prognosis across a spectrum of malignant disorders of different primary location. Neopterin concentration in peripheral blood as well as in the tumor microenvironment correlates with phenotypic and functional changes of lymphocytes, indicating immune dysfunction. Increased neopterin concentrations are also accompanied by increased rate of conversion of tryptophan to kynurenine. Increasing neopterin concentrations also accompany side effects of anticancer treatment and could predict subsequent complications. Although almost four decades have elapsed since the discovery of increased neopterin concentrations in cancer patients, the full potential of neopterin as a biomarker in this setting has not been so far realized.
Keywords: neopterin; Kynurenine; tryptophan